(untitled) (Al-Academy, 2024)
The research titled (Reduction in Contemporary Iraqi Sculptural Formation) deals with the phenomenon of formal reduction of sculpture and its formation in contemporary Iraqi sculptural formation. The research consists of an introduction to the research and several chapters, where the first chapter presented the problem of the research, its importance, its objectives, and the definition of its terms, and the second chapter represented the theoretical framework, which came from two sections, the first of which is reductionism in modern sculpture and the second of which is the contemporary formation movement. The third chapter is a chapter on research procedures and analysis of its sample, where the researcher took and analyzed four examples of contemporary Iraqi sculptural formation. The fourth chapter included: the research results, the most important of which were the following: - 1- The presence of shorthand features in contemporary Iraqi sculptural formation gives an indication of the style of the individual artist in terms of style, technique, type, and type of word chosen for expression through the apparent differences in the type of work presented, as stated in all samples of the sample. 2- Much of the impact of environmental and social differences on the expression of some of the sample’s models emerged, which resulted in a variety of methods of reduction in contemporary Iraqi sculptural formation. 3- The diversity of reduction in contemporary Iraqi sculptural formation based on the difference in the expressive performance of reduction in documenting the idea. 4- Through the characteristic of reductionism in contemporary Iraqi sculptural formation, the Iraqi sculptor achieved by conveying a message to the recipient that he is liberated from the characteristic of limitation in expression and the type of work he wants to work on, in addition to open freedom with deep dimensions in interpretation, perception, and reception of the concepts of a single work. 5- Reduction in contemporary Iraqi sculptural formation emphasized the forms of circulating discourses, examining within them a pluralism in style, meaning, and social and historical evidence.